Upaya Meningkatkan Motivasi Belajar Matematika Siswa SD Melalui Optimasi Game “Moving Twins” - Sa'adah, Miratus; Ningsih, Helen Widiya Kusuma; Ma'rifah, Shokifatul; Saputri, Amalia Mulya; Ilmiyah, Nazril; Avita; Rahayu, Puji (Jurnal Riset Pembelajaran Matematika, 2024)
Elementary school (SD) students must possess fundamental mathematical abilities. One of them is the capacity to execute numerical calculation procedures. Evidence from the field indicates that the academic performance of primary school kids in mathematics remains at a poor level. This occurs due to the constraints imposed by teachers on pupils' activities at school, leading to a rapid onset of boredom during the learning process. Hence, it is imperative to establish a novel educational environment by leveraging media tools to enhance the enjoyment and dynamism of the learning process. The learning method "MOVING TWINS" will be utilized. The objective of this study is to enhance the learning motivation of primary school children in the subject of arithmetic operations by utilizing the Moving Twins game. The participants of this study consisted of elementary school kids, selected using the purposive sampling technique. This study employs a pre-experimental design known as a one group pretest-posttest design. The research findings indicate that employing the Moving Twins Game can enhance the learning motivation of primary school pupils in the domain of number counting operations. Keywords: Learning Motivation, Arithmetic Operations, Moving Twins Game.